Management of mandibular flat ridge using modified suction-effective method in geriatric patient - Leonita, Luluk LA.; Kusdhany, Lindawati S. (Indonesian Journal of Prosthodontic, 2025)
Background: Geriatric patient has compromised medical conditions, physical disability, and cognitive impairment, thus the treatment plan must consider many factors both local and systemic condition of the patient. The main problem that often arises when treating edentulous patients, especially in elderly patients, is severe mandibular ridge resorption. This makes it difficult to achieve retention and stabilization of the mandibular complete denture. One technique to overcome this problem is using suction effective mandibular complete denture introduced by Dr. Jiro Abe. This method can provide sealing of the entire denture border including the retromolar pad area. Objectives: This report aimed to elaborate the management of flat mandibular ridge using modified suction-effective method in geriatric patient. Case report: A 71-year-old male geriatric patient with fully edentulous teeth came with history of hypertension and high risk of falling. The patient had never used any denture before and wanted to be able to eat properly and seek improvement in appearance. The mandibular showed highly resorbed ridge along with spongious tissue. Modification of this technique carried out by utilizing semi-adjustable articulator and the use of bite rim mounted on custom tray which facilitated closed-mouth impression that is in accordance with patient’s functional movement in occlusion state. Conclusion: Rehabilitation of complete denture in elderly patients must consider efficient and appropriate method according to the patient's systemic and local conditions. Flat ridge management in geriatric patient using semi-adjustable articulator and modified suction-effective method can provide retention and stability in mandibular complete denture.